The pivotal regulatory role of the FEV-SLC7A11 axis in ferroptosis elucidates the anti-aging mechanism of β-sitosterol in a cross-species study - Fang, Zhihan; Xie, Liyao; Wang, Jing; Li, Junyi; Pan, Yirui; Chen, Lei; Cao, Shuyi; Zhou, Qi; Li, Shaobin; Zhang, Chao; Li, Li (Frontiers in Pharmacology, 2025)
Traditional Chinese medicine is a valuable source of bioactive compounds for combating aging. Among these, β-sitosterol (BS), a sterol extracted from Alpiniae oxyphyllae fructus, has attracted attention for its potent antioxidant, anti-inflammatory, and free radical scavenging properties. However, its precise anti-aging mechanism remains unclear. Here, we aimed to elucidate how BS influences cellular and murine aging. Preliminary studies in Caenorhabditis elegans (C. elegans) showed that BS modulates intracellular oxidative stress via the transcription factor ETS-5. Building on this, we established an aging model in human umbilical vein endothelial cells by treating them with 200 μM H2O2, assessing senescence via β-galactosidase staining and oxidative stress by measuring reactive oxygen species, malondialdehyde, and the GSH/GSSG ratio. Both in vitro and in vivo experiments revealed that BS treatment significantly alleviated oxidative stress, upregulated ferroptosis-related proteins, and suppressed ferroptosis to mitigate cellular senescence. Furthermore, RNA interference targeting fev, the human homolog of ets-5, reduced oxidative stress, and subsequent BS treatment further enhanced this protective effect. Dual luciferase assays indicated that FEV functions as a transcriptional repressor of SLC7A11; BS treatment altered FEV expression, thereby promoting SLC7A11 expression and facilitating the nuclear import of reduced glutathione. In summary, our results indicate that BS modulates FEV expression to regulate intracellular oxidative stress, suppress ferroptosis, and alleviate aging phenotypes. Our multi-model approach, integrating insights from C. elegans, human endothelial cells, and murine systems, substantially enhances the robustness and translational potential of these findings.